IADC/SPE Drilling Conference 2008
DOI: 10.2118/112536-ms
|View full text |Cite
|
Sign up to set email alerts
|

Extended-Reach Drilling Offshore California: An Operator's Experience with Drilling a Record Extended Reach Well

Abstract: The "Spanish Bay" well was drilled from a production platform located offshore California in 1,075 ft of water. This record setting extended reach well overcame numerous technical and operational challenges and reached a total depth of 33,435-ft measured depth (MD) / 7,663-ft true vertical depth (TVD) with 29,720-ft displacement. This paper will highlight the rig package limitations and upgrades, describe key technical and operational challenges, discuss how the challenges were addressed, and describe key / un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…This presents unique set of challenges not seen in new field developments with world class ERD wells ( (Elks et al, 2002;Walker 2008;Armstrong et al, 2011;McDermott et al, 2005;Viktorin et al, 2006;Elsborg et al, 2005;Woodfine et al, 2011;Cocking et al, 1997;Nughaimish et al, 2009). The new redrilled wells were the third wells to be drilled from their respective platform slot.…”
Section: Learning From Three-well Erd Program Donor Well (Slot) Risk mentioning
confidence: 99%
See 2 more Smart Citations
“…This presents unique set of challenges not seen in new field developments with world class ERD wells ( (Elks et al, 2002;Walker 2008;Armstrong et al, 2011;McDermott et al, 2005;Viktorin et al, 2006;Elsborg et al, 2005;Woodfine et al, 2011;Cocking et al, 1997;Nughaimish et al, 2009). The new redrilled wells were the third wells to be drilled from their respective platform slot.…”
Section: Learning From Three-well Erd Program Donor Well (Slot) Risk mentioning
confidence: 99%
“…The company has global experience in new field developments with world class ERD wells (Elks et al, 2002;Walker 2008;Armstrong et al, 2011; McDermott et al, 2005;Viktorin et al, 2006; Elsborg et al, 2005;Woodfine et al, 2011) and the different approaches for new wells and redrilled wells will be compared.The paper will show how the challenges of ERD operations to 25 kft in a 6-in. The upgrade of the rig in two separate projects allowed the lessons learned from the first extended reach drilling (ERD) upgrade (Cutt 2007) to be applied to the second 10-ksi upgrade.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The drilled Xijiang 24-3-A20 ERW had a vertical depth of 2851.24 m and a horizontal displacement of 7825.51 m [12]. In 2007, ExxonMobil drilled an ERW with a vertical depth of 2336 m and a horizontal displacement of 9059 m off the coast of California, setting a new record for the global offshore ERW [13]. Chenghai 1 area of Dagang Oilfield in China utilized Chenghai 1 offshore artificial island to develop a marginal oilfield 5500 m offshore with ERWs, among which the maximum horizontal displacement reached 5454 m, and the maximum ratio of horizontal displacement to vertical depth was 5.41 [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Naegel et al [5] reported an ERD well with a 20,341.2 ft horizontal departure at 5,577 ft true vertical depth (TVD). ERD continued in the past two decades with new record updated every a few years [6][7][8][9][10][11]. Armstrong and Evans [12] reported planning and execution of an offshore ERD well of a total measured depth (MD) of 37,165 ft with TVD of 6,938 ft, and horizontal displacement (HD) of 33,682 ft. Tskhadaya et al [13] presented a design of ERD for an Arctic well depth of 49,212.6 ft and horizontal borehole depth of 4,921.3 ft. Special technical issues in ERD include rig requirement, borehole stability, cuttings transport, data acquisition, and drill string design.…”
Section: Introductionmentioning
confidence: 99%